Pengembangan Modul Ajar PAI Elemen Akhlak Fase E Kurikulum Merdeka - Ardiyan, Riris; Wulandari, Kartika (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
ABSTRACT This research aims to develop learning media in the form of PAI Teaching Modules for Moral Elements of Phase E of the Independent Curriculum, as well as to determine the feasibility of PAI Teaching Modules for Moral Elements of Phase E of the Independent Curriculum. This research is a type of development research or also called Research and Development (R & D). This development model includes 5 stages, namely: Research and information collecting, Planning, Develop preliminary form of product, Preliminary testing, Main product revision. At this development stage the feasibility of the PAI Teaching Module for the Moral Elements of Phase E of the Independent Curriculum is assessed by 1 media expert and 2 material experts. Data collection uses qualitative analysis, namely determining problems and quantitative in the form of a questionnaire in the PAI Teaching Module Moral Elements of the Independent Curriculum. The results of the validity test by media experts obtained a score of 97.89 which is included in the very feasible category. The results from 2 media experts obtained scores of 76.66 and 80 which were included in the feasible category. KEYWORDS: Development of Teaching Modules, Elemen Akhlak, Independent Curriculum. ABSTRAK Penelitian ini bertujuan mengembangkan media pembelajaran berupa Modul Ajar PAI elemen Akhlak Fase E Kurikulum Merdeka, serta mengetahui kelayakan Modul Ajar PAI elemen Akhlak Fase E Kurikulum Merdeka. Penelitian ini merupakan jenis penelitian pengembangan atau disebut juga dengan Research and Development (R & D). Model pengembangan ini meliputi 5 tahap yaitu: Research and information collecting, Planning (perencanaan),Develop preliminary form of product, Preliminary testing, Main product revision. Tahap Pengembangan kelayakan Modul Ajar PAI elemen Akhlak Fase E Kurikulum Merdeka dinilai oleh 1 ahli media dan 2 ahli materi. Pengumpulan data menggunakan analisis kualitatif yaitu menentukan permasalahan dan kuantitatif yang berupa angket pada Modul Ajar PAI Elemen Akhlak Kurikulum Merdeka. Hasil uji validitas oleh ahli media memperoleh hasil skor 97,89 yang termasuk dalam kategori sangat layak. Hasil dari 2 Ahli media memperoleh hasil skor 76,66 dan 80 yang termasuk dalam kategori layak. KATA KUNCI: Pengembangan Modul Ajar, Elemen Akhlak, Kurikulum Merdeka